MiR-27a and miR-27b regulate autophagic clearance of damaged mitochondria by targeting PTEN-induced putative kinase 1 (PINK1). Issue 1 (December 2016) - Kim, Jaekwang; Fiesel, Fabienne; Belmonte, Krystal; Hudec, Roman; Wang, Wang-Xia; Kim, Chaeyoung; Nelson, Peter; Springer, Wolfdieter; Kim, Jungsu
Abstract Background Loss-of-function mutations inPINK1 andPARKIN are the most common causes of autosomal recessive Parkinson's disease (PD). PINK1 is a mitochondrial serine/threonine kinase that plays a critical role in mitophagy, a selective autophagic clearance of damaged mitochondria. Accumulating evidence suggests mitochondrial dysfunction is one of central mechanisms underlying PD pathogenesis. Therefore, identifying regulatory mechanisms of PINK1 expression may provide novel therapeutic opportunities for PD. Although post-translational stabilization of PINK1 upon mitochondrial damage has been extensively studied, little is known about the regulation mechanism of PINK1 at the transcriptional or translational levels. Results Here, we demonstrated that microRNA-27a (miR-27a) and miR-27b suppress PINK1 expression at the translational level through directly binding to the 3′-untranslated region (3′UTR) of its mRNA. Importantly, our data demonstrated that translation of PINK1 is critical for its accumulation upon mitochondrial damage. The accumulation of PINK1 upon mitochondrial damage was strongly regulated by expression levels of miR-27a and miR-27b. miR-27a and miR-27b prevent mitophagic influx by suppressing PINK1 expression, as evidenced by the decrease of ubiquitin phosphorylation, Parkin translocation, and LC3-II accumulation in damaged mitochondria. Consequently, miR-27a and miR-27b inhibit lysosomal degradation of the damaged mitochondria, as shown by the decrease of the delivery of damaged mitochondria to lysosome and the degradation of cytochrome c oxidase 2 (COX2), a mitochondrial marker. Furthermore, our data demonstrated that the expression of miR-27a and miR-27b is significantly induced under chronic mitophagic flux, suggesting a negative feedback regulation between PINK1-mediated mitophagy and miR-27a and miR-27b. Conclusions We demonstrated that miR-27a and miR-27b regulate PINK1 expression and autophagic clearance of damaged mitochondria. Our data further support a novel negative regulatory mechanism of PINK1-mediated mitophagy by miR-27a and miR-27b. Therefore, our results considerably advance our understanding of PINK1 expression and mitophagy regulation and suggest that miR-27a and miR-27b may represent potential therapeutic targets for PD.